Mükemmel Halkla İlişkiler Bağlamında Kültürlerarası İletişim Stratejilerinin Uygulanması Ve Yerel Yönetimler Açısından Önemi - POYRAZ, EMEL (My University, 2022)
Intercultural communication is the most accurate tool that enables communities to explain their own cultures to others, to live together and peace. It is a fact that culture also affects public relations since public relations is basically a communication activity. Culture also affects and is influenced by communication. Thus, there is a need to conceptually relate culture to public relations. In this context, the increasing importance of intercultural interactions and socio-cultural differences have made communication strategies and public relations activities more important for a successful social life in societies with different cultures. In this context, in this study, the public relations strategies implemented by local governments as a local actor of a multicultural city within the scope of intercultural communication activities for citizens of various ethnicities living in the city were investigated in order to achieve cultural harmony. In this context, starting from different practices and approaches in public relations, it has been tried to reveal how can local governments benefit from these public relations approaches and methods about the management of cultural diversity, and a model for putting forward a functional public relations strategy in the context of excellence theory has been proposed. Keywords: Excellence theory in public relations, Intercultural communication, Local governments

Kültürlerarası iletişim, toplumların kendi kültürlerini diğer toplumlara anlatabilmelerini, anlaşabilmelerini ve barış içinde yaşayabilmelerini sağlayan en doğru araçtır. Halkla ilişkiler ise temelde bir iletişim faaliyeti olduğundan, kültürün halkla ilişkileri de etkilediği bir gerçektir. Kültür iletişimi etkiler ve ondan etkilenir. Dolayısıyla, kültürü halkla ilişkilerle kavramsal olarak ilişkilendirmeye ihtiyaç vardır. Bu bağlamda, kültürlerarası etkileşimlerin giderek daha fazla yaşanması ve sosyo-kültürel farklılıkların giderek daha fazla önem kazanması, farklı kültürlere sahip toplumlarda başarılı bir sosyal yaşam için iletişim stratejileri ve halkla ilişkiler faaliyetlerini daha önemli hale getirmiştir. Bu kapsamda bu çalışmada kültürel uyum sağlamada yerel yönetimlerin çokkültürlü bir kentin yerel aktörü olarak kentte yaşayan çeşitli farklı etnik yapıdaki vatandaşlarına yönelik kültürlerarası iletişim çalışmaları kapsamında gerçekleştirdikleri halkla ilişkiler stratejileri araştırılmıştır. Bu kapsamda halkla ilişkilerdeki farklı uygulamalar ve yaklaşımlardan yola çıkılarak, kültürel çeşitliliklerin yönetimi hakkında yerel yönetimlerin söz konusu halkla ilişkiler yaklaşım ve yöntemlerinden nasıl faydalandığı ve faydalanabileceği ortaya koymaya çalışılarak, mükemmellik teorisi bağlamında işlevsel bir halkla ilişkiler stratejisi ortaya konulmaya yönelik bir model öne sürülmüştür. Anahtar Kelimeler: Mükemmel halkla ilişkiler, Kültürlerarası iletişim, Yerel yönetimler
The Mission Of Public Relations On Intercultural Communication; A Research On Local Governments Management Of Cultural Diversity
Keywords: Mükemmel halkla ilişkiler; Kültürlerarası iletişim; Yerel yönetimler; Excellence theory in public relations; Intercultural communication; Local governments